An investigation of the impact of Facebook and Instagram on consumer buying behaviour: The case of retail fashion consumers in Rhodes, Greece - Phaedra Clarke; Dionisia Tzavara; Fotios Misopoulos (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2019)
Purpose: The aim of this paper is to explore the impact of Facebook and Instagram on consumer buying behaviour in the retail fashion market in Rhodes, Greece. We look at the extent to which the two social media influence Rhodian consumer preferences toward certain stores and at whether Rhodians use these social media for fashion information and inspiration. Design/methodology/approach: The study is conducted online, using quantitative methodology and close-ended survey questionnaires to obtain data. Finding: We find that Facebook and Instagram influence Rhodian consumer behaviour. Rhodians believe that the two social media are a good way to follow fashion trends and that fashion is more accessible because of Facebook and Instagram compared to five years ago. The Rhodians seem to be getting fashion inspiration from Facebook and/or Instagram but more in a passive manner than through active engagement with fashion on the two social media. Research limitations/implications: Our findings demonstrate that Facebook and Instagram are very powerful in bringing fashion closer to consumers and they underline the role that these social media can plan in the marketing mix. Our findings can be used by fashion retailers to inform their social media engagement strategies and decisions. Our research can be extended to investigate the impact of different social media constructs on consumer behaviour and to look at what type of social media content may be more impactful in shaping shopping behaviour. Originality/value: Research on the subject of how social media impacts the behaviour of fashion consumers in Greece is limited and literature on the retail fashion market is noticeably scarce. Studies published on the topic of social media influencing consumer decisions with a focus on the Greek market are almost exclusively confined to the tourism sector. Our findings can be used by fashion retailers to inform their social media engagement strategies and decisions.
Keywords: M30; M31; M39; 330; Consumer Buying Behaviour; Social Media Marketing; Retail Fashion; Greece